Education, Gender, and Identity: A Scoping Review of Young Muslim Experiences in Multicultural Contexts - Maulana Perdana (Journal of Islamic Psychology, 2025)
This scoping review synthesizes multidisciplinary evidence on young Muslims' experiences across schools, universities, and nonformal learning contexts, focusing on the intersection of education, gender, and identity. Guided by Arksey and O’Malley’s framework and reported in line with PRISMA-ScR, the review canvassed Scopus, Web of Science, ERIC, PsycINFO, PubMed, and gray literature (2000–2024). Included studies, spanning qualitative, quantitative, and mixed-methods designs, involved participants aged 12–25 in Muslim-majority and Muslim-minority settings. Data were organized in a charting matrix and examined through descriptive and thematic analyses. Results highlight fluid and hybrid identities, a strong link between belonging and mental health/academic performance, and the tangible effects of Islamophobia, discrimination, and microaggressions. Gendered dynamics are salient—from heightened visibility for hijab-wearing women to securitized masculinity stereotypes for young men. Additional drivers include intersectional positioning, family/community influence, multiperspectival curricula, culturally responsive teaching, religious accommodations, and the digital ecosystem. Promising practices encompass anti-bias professional development, pluralistic curriculum design, confidential reporting systems, pragmatic accommodations, mentoring, and collaborative co-curricular programs. The review underscores the need to recalibrate identity models around hybridity, safety, and intersectionality; reinforce anti-discrimination governance; build educator capacity; strengthen family–community partnerships; and adopt data-driven monitoring. Future work should emphasize longitudinal and experimental studies, cross-cultural validation, participatory approaches, and context-sensitive digital literacy initiatives, noting the literature's skew toward the Global North.